Inonotus hispidus (Bull.) P. Karst. - bioecological characteristics, significance and possibility of use for medical purposes (medicinal properties) - Radulović Zlatan; Karadžić Dragan; Milenković Ivan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
Inonotus hispidus develops as a parasite on living trees and causes white, central rot. Infections occur through injuries on branches or stems. Its ability to cause cankers differentiates it from fungi that only cause heart rot. In Serbia, it is quite frequent on Persian walnut (Juglans regia), black walnut (Juglans nigra), plane tree (Platanus acerifolia) or common ash (Fraxinus excelsior). In urban conditions, apart from plane trees, carpophores sometimes occur on horse chestnut (Aesculus hippocastanum), sycamore maple (Acer pseudoplatanus), Turkey oak (Quercus cerris) and some fruit trees (e.g. Malus spp.). The colony of this fungus in media amended with gallic and tannic acid shows a positive oxidase reaction (the diffusion zone is dark brown, opaque, spread over a considerable distance from the colony’s periphery, with equal intensity on media with gallic and tannic acid). After seven days of incubation, the growth of the colony on the medium with gallic acid is in traces, while the diameter of the colony on the medium with tannic acid is between 1-2 cm and based on this, this fungus is classified in the 5th group according to Davidson et al. (1938). The fungus I. hispidus has a large number of compounds that have potential applications in the treatment of various diseases in humans, commonly in the treatment of various types of cancer.